Jack and the beanstalk - Beneduce, Ann Keay.; e (New York : Philomel Books, 1999)
A boy climbs to the top of a giant beanstalk, where he uses his quick wits to outsmart an ogre and make his and his mother's fortune.
Wilson's Children.
School Library Journal.
Book Links (A.L.A.).
4.7
K-3
Keywords: Fairy tales; Folklore -- England; Fairy tales; Folklore; Fairy tales; Folklore -- England; Fairy tales; Folklore -- England